Capital Account Liberalization Indices: A Review of Literature - Kalsie, Anjala; Kalra, Jappanjyot Kaur; Dhamija, Jyoti (Journal of Advances in Management Sciences & Information Systems, 2022)
The complexities of the global financial system have been increasing and the same is managed by implementation of capital controls by the nations. Therefore, it is important to understand what controls are and how the nations implement them. The aim of this paper is to analyze and understand the capital controls indices developed so far to measure financial openness or liberalization. Broadly the measures developed so far are categorized into de facto, de jure and hybrid measures. Each measure constructed has used different scale and hence the intensity and description of each measure is different also they cover different countries.